ANALISIS KONSEP INSAN KAMIL DALAM TUJUAN PENDIDIKAN ISLAM DI ERA MODERN - Carissa Imelda Salsabila Kusuma; Vina Rohmatul Ummah; Zaitun Ummul Khoiroh; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The rapid development of digital technology has significantly influenced the character formation of students in Madrasah Ibtidaiyah (Islamic elementary schools), particularly through the emergence of moral and ethical crises characterized by declining respect for teachers and parents, weakened self-control, and reduced spiritual awareness. This condition reflects a shift in educational orientation that prioritizes academic achievement over character and personality development. This study aims to analyze the concept of Insan Kamil within the framework of Islamic educational objectives and examine its relevance as a solution to the moral challenges faced by students in the digital era. This research employs a library research method using data derived from books, scientific journals, and educational documents related to Islamic education, the concept of Insan Kamil, and character education. The collected data were analyzed using content analysis techniques through the processes of identification, categorization, and interpretation of relevant themes. The findings indicate that the concept of Insan Kamil remains highly relevant as an Islamic educational paradigm that promotes a balance between intellectual, spiritual, moral, and social dimensions. Its implementation can be carried out through strengthening ta’dib (adab education), digital role modeling by teachers, character-based evaluation systems, and collaboration between schools and families. Therefore, the integration of digital technology and adab education is a strategic approach to developing knowledgeable, morally upright, and highly integrated generations in accordance with the goals of Islamic education.